LEGAL AND METHODOLOGICAL ASPECTS OF GEOLOGICAL AND ECONOMIC ASSESSMENT OF MINERAL RESERVES AND RESOURCES IN UKRAINE: STATUS AND PROSPECTS - LYTVYNIUK, Stanislav; PAIUK, Sergii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Practical application analysis of geological and economic assessment (GEA) results, its legal features and methodological support have been provided. Peculiarities associated with different GEA stages, purposes and objects have been considered during the analysis. The current state of geological study and analysis of subsoil use in Ukraine proves the regulatory and practical significance of geological and economic assessment of all stages for various types of special permits. Geological and economic assessment results ensure the State Balance of Mineral Reserves being updated with relevant information for further resource management. The authors' research has determined peculiarities of current requirements for geological and economic assessment, which require revision and alignment (adaptation) with regulatory and methodological standards used by the world's leading countries in the mining sector. Further directions for the assessment methodology development based on components of the geological and feasibility study of reserves and resources considering the experience in state expertise of geological and economic assessment materials on various minerals have been determined in the article.
Keywords: geological and economic assessment; mineral deposits; geological exploration stages; commercial significance; feasibility study